Pengembangan Modul Rainbow, Metode Akselerasi Konstektual Belajar Bahasa Inggris Melalui Ekstrakurikuler - Erika Septiana Dewi; Krista Mala Oktaviani; Inka Fitri Milenia; Lena Wahyu Triasna Alviana (Jurnal Administrasi Pendidikan, 2022)
The purpose of this research is to develop the Rainbow Method, contextual acceleration of learning English through extracurricular activities, it also tested the effectiveness of the rainbow method in increasing the creativity of students in learning English. The research design used is research and development. The steps include: initial research, planning, initial product development, initial trials, product revisions, field trials, final product revisions, and determination and implementation. The results of this study indicate that the rainbow module is suitable for use in the learning process at Alepho extracurricular at SMA Negeri 1 Boyolangu. In addition, the module is also effective in increasing students' understanding of the material presented by the teacher. Therefore, this Rainbow Module can be used as a supplement or addition to learning activities for students.